Photoswitching Studies of New Photochromic Ionic Liquids Studied in Real Time by in Situ Irradiation - Aspee-Lamas, A; Barrías-González, P (ROYAL SOC CHEMISTRY, 2022)
The photoswitching behavior of new double cationic azobenzene derivatives AZO(pyr) and AZO(imid) was studied by in situ irradiation in the cavity of a H-1-NMR spectrometer. The setup of the experiments allowed us to easily collect, in real-time, valuable spectral information to quantify the concentration of photoisomers without deconvolution of the data. With this information, the equilibrium constant and thermodynamics parameters of the photoinduced equilibrium at the photostationary state could be determined. At the same time, this type of experiment also allowed us to obtain precise structural information (i.e., chemical shift, integration, and constant coupling of each isomer) based on the pattern of the signals of the H-1-NMR spectra of the photoswitches. The same irradiation system was utilized to study the fatigue of the cationic AZO(pyr) and AZO(imid) in several solvents, finding that these probes are photostable in methanol, dimethyl sulfoxide, and propyl ammonium formate.